Glucocorticoid replacement therapy for primary and secondary adrenal insufficiency and their impact on cognition - Harbeck, Birgit; Kropp, Peter; Kreitschmann-Andermahr, Ilonka (Frontiers in Endocrinology, 2023)
Patients with adrenal insufficiency (AI) are treated with conventional or modified-release glucocorticoid (GC) replacement therapy (GRT). Although current GRT regimens aim to mimic the physiological circadian pattern of cortisol secretion, temporary phases of hypo- and hypercortisolism are common. There is good evidence, that prolonged phases of hypo- or hypercortisolism are associated with impaired cognitive functioning. However, little is known about cognitive functioning in patients with AI regarding the effects of dosage and duration of glucocorticoid replacement therapy. There is also little data available comparing the effects of GC therapy on patients with primary and secondary forms of AI as well as with respect to different formulas. This Mini-Review gives an overview of the current studies on GRT for primary and secondary AI and their impact on cognition. Strengths and weaknesses of the studies and their Implications for clinical daily routine are discussed with a special emphasis on practical considerations for the treating endocrinologist.